Water quality studies at water treatment plant in Precinct 19, Putrajaya / Noraziah Khalid - Khalid, Noraziah (2007)
A study of water quality at 6 different stages at WTP was carried out at Precinct 19, Putrajaya. Water Quality was determined by specific parameter such as BOD, COD, DO, NHз-N, SS, pH and temperature. Results show that most of the parameters studied are still below the permissible standard drinking water recommended by Interim National Water Quality Standards for Malaysia (INWQS). The results also show that water quality of raw water is moderate (Class III) and the other 5 stages (coagulation, flocculation, sedimentation, filtration and disinfection) are good (Class II).